Ambient‐Dried, 3D‐Printable and Electrically Conducting Cellulose Nanofiber Aerogels by Inclusion of Functional Polymers. (3rd February 2020) - Françon, Hugo; Wang, Zhen; Marais, Andrew; Mystek, Katarzyna; Piper, Andrew; Granberg, Hjalmar; Malti, Abdellah; Gatenholm, Paul; Larsson, Per A.; Wågberg, Lars
Abstract: This study presents a novel, green, and efficient way of preparing crosslinked aerogels from cellulose nanofibers (CNFs) and alginate using non‐covalent chemistry. This new process can ultimately facilitate the fast, continuous, and large‐scale production of porous, light‐weight materials as it does not require freeze‐drying, supercritical CO2 drying, or any environmentally harmful crosslinking chemistries. The reported preparation procedure relies solely on the successive freezing, solvent‐exchange, and ambient drying of composite CNF‐alginate gels. The presented findings suggest that a highly‐porous structure can be preserved throughout the process by simply controlling the ionic strength of the gel. Aerogels with tunable densities (23–38 kg m −3 ) and compressive moduli (97–275 kPa) can be prepared by using different CNF concentrations. These low‐density networks have a unique combination of formability (using molding or 3D‐printing) and wet‐stability (when ion exchanged to calcium ions). To demonstrate their use in advanced wet applications, the printed aerogels are functionalized with very high loadings of conducting poly(3, 4‐ethylenedioxythiophene):tosylate (PEDOT:TOS) polymer by using a novel in situ polymerization approach. In‐depth material characterization reveals that these aerogels have the potential to be used in not only energy storage applications (specific capacitance of 78 F g −1 ), but also as mechanical‐strain and humidity sensors. Abstract : This study presents a novel, fast, and green way of preparing cross‐linked, ambient‐dried aerogels made from cellulose nanofibers and alginate. It further demonstrates the preparation of 3D‐printed aerogels with tailorable shapes, structures, and mechanical properties. The aerogels are herein functionalized with electrically conducting poly(3, 4‐ethylenedioxythiophene) to demonstrate their potential use in the fields of energy storage and sensing.